Imams’ Delusions in Confusing Hadiths - An Analytical Study (The International Journal for Scientific Research, 2023)
Praise be to God, and may blessings and peace be upon the Messenger of God and upon his family and all his companions, and after:This is a summary of the research entitled: The Imams’ Delusions in Confusing Hadiths - An Analytical Study.The research included an introduction, which included: the problem of the study, its objectives, its importance, the limits of the research, the methodology of the study, the terminology of the study, previous studies, then the illusions of the imams in confusing the hadiths, and it includes three topics:The first topic: Illusions related to combining two narratives in one hadith.The second topic: Illusions related to reversing a chain of transmission onto another text.The third topic: Illusions related to attributing a narration to someone other than its narrator.Then I concluded the research with a conclusion that included the most important results and recommendations, then an index of sources and references.In conclusion, I ask God to benefit from this study, and may God’s blessings and peace be upon our Prophet Muhammad and his family and companions.
Keywords: Illusions; Ibn Al-Mawaq; Hadith; Al-Ishbili; Ibn Al-Qattan; Chain of Transmission